Healing logics : culture and medicine in modern health belief systems - Brady, Erika, 1952- (Utah State University Press, 2001)
"Scholars in folklore and anthropology are more directly involved in various aspects of medicine--such as medical education, clinical pastoral care, and negotiation of transcultural issues--than ever before. Old models of investigation that artificially isolated "folk medicine," "complementary and alternative medicine," and "biomedicine" as mutually exclusive have proven too limited in exploring the real-life complexities of health belief systems as they observably exist and are applied by contemporary Americans. Recent research strongly suggests that individuals construct their health belief systmes from diverse sources of authority, including community and ethnic tradition, education, spiritual beliefs, personal experience, the influence of popular media, and perception of the goals and means of formal medicine. Healing Logics explores the diversity of these belief systems and how they interact--in competing, conflicting, and sometimes remarkably congruent ways. This book contains essays by leading scholars in the field and a comprehensive bibliography of folklore and medicine."--Publisher's description